Hereditary Spastic Paraplegia Type 43 (SPG43) is Caused by Mutation in C19orf12. Issue 10 (12th August 2013) - Landouré, Guida; Zhu, Peng‐Peng; Lourenço, Charles M.; Johnson, Janel O.; Toro, Camilo; Bricceno, Katherine V.; Rinaldi, Carlo; Meilleur, Katherine G.; Sangaré, Modibo; Diallo, Oumarou; Pierson, Tyler M.; Ishiura, Hiroyuki; et al.
<x xml:space="preserve">Abstract</x> We report a Malian and Brazilian families affected with hereditary spastic paraplegia (SPG43) and "forme frustre" neurodegeneration with brain iron accumulation (NBIA), respectively. The same mutation (C19orf12, p.Ala63Pro) and haplotype were found in these families, but MRI scans showed no brain iron deposition in the Malian subjects. Heterologous expression of this SPG43 and NBIA variant resulted in alteration in the subcellular distribution of C19orf12. Further studies are needed to unravel other genetic or environmental factors underlining these phenotypic differences. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>